Exploring the etiology of dilated cardiomyopathy using Mendelian randomization - Xue, SiYang; Jiang, HongJu (Frontiers in Cardiovascular Medicine, 2024)
Background: Observational clinical studies suggest associations between dilated cardiomyopathy (DCM) and various factors including Titin, CTnI, Desmocollin-2, the perinatal period, alcohol, Behçet's disease, systemic lupus erythematosus, hyperthyroidism and thyrotoxicosis, hypothyroidism, Carnitine metabolic disorder, and renal insufficiency. The causal nature of these associations remains uncertain. This study aims to explore these correlations using the Mendelian randomization approach. Objective: To investigate the etiology of DCM through Mendelian randomization analysis. Methods: Data mining was conducted in genome-wide association study (GWAS) databases, focusing on variant target proteins (Titin, CTnI, Desmocollin-2), the perinatal period, alcohol, Behçet's disease, systemic lupus erythematosus, hyperthyroidism and thyrotoxicosis, hypothyroidism, Carnitine metabolic disorder, and renal insufficiency, with DCM as the outcome. The analysis employed regression models such as Inverse Variance Weighted (IVW), MR-Egger, Simple Mode, Weighted Median, and Weighted Mode. Results: IVW results showed a correlation between Titin protein and DCM, identifying Titin as a protective factor [OR=0.856, 95%CI (0.744, 0.985), P=0.030]. CTnI protein correlated with DCM, marking it as a risk factor [OR=1.204, 95%CI (1.010, 1.436), P=0.040]. Desmocollin-2 also correlated with DCM, recognized as a risk factor [OR=1.309, 95%CI (1.085, 1.579), P=0.005]. However, no causal relationship was found between the perinatal period, alcohol, Behçet's disease, systemic lupus erythematosus, hyperthyroidism and thyrotoxicosis, hypothyroidism, Carnitine metabolic disorder, renal insufficiency, and DCM (P>0.05). The MR-Egger intercept test indicated no pleiotropy (P>0.05), affirming the effectiveness of Mendelian randomization in causal inference. Conclusion: Titin, CTnI, and Desmocollin-2 proteins are identified as independent risk factors for DCM. Contrasting previous observational studies, no causal relationship was observed between the perinatal period, alcohol, Behçet's disease, systemic lupus erythematosus, hyperthyroidism and thyrotoxicosis, hypothyroidism, Carnitine metabolic disorder, renal insufficiency,and DCM.